Adaptation-Driven Evolution of Sirtuin 1 (SIRT1), a Key Regulator of Metabolism and Aging, in Marmot Species - Junker, Nora; Gossmann, Toni I. (Frontiers in Ecology and Evolution, 2021)
The sirtuin protein family plays a role in the lifespan of various species and is involved in numerous key metabolic processes. To understand the evolutionary role of sirtuins in marmots, a long-living rodent species group with remarkable metabolic shutdown during hibernation, we conducted a phylogeny-based substitution rate analysis of coding genes based on genetic information of seven marmot species. We show that sirtuin 1 (SIRT1) has evolved under positive selection in the marmot lineage. We pinpoint three amino acid changes in four different marmot species that underlie the signal of positive selection and that may favor increased longevity in marmots. Based on a computational structural analysis we can show that all three substitutions affect the secondary structure of the same region in human SIRT1. We propose that the identified region is close to the catalytic domain and that the potential structural changes may impact the catalytic activity of the enzyme and therefore might be playing a functional role in marmot’s extended lifespan and metabolic shutdown.